Clinical Features and Management of Women with Borderline Ovarian Tumors in a Single Center in Brazil - Yoshida, Adriana; Tavares, Bárbara Virginia Gonçalves; Sarian, Luís Otavio; Andrade, Liliana Aparecida Lucci Ângelo; Derchain, Sophie Françoise (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The aim of the present study was to describe and analyze data of 57 women with borderline ovarian tumors (BOTs) regarding histological characteristics, clinical features and treatment management at the Department of Obstetrics and Gynecology of the Universidade Estadual de Campinas (Unicamp, in the Portuguese acronym).Methods The present retrospective study analyzed data obtained from clinical and histopathological reports of women with BOTs treated in a single cancer center between 2010 and 2018.Results A total of 57 women were included, with a mean age of 48.42 years old (15.43–80.77), of which 30 (52.63%) were postmenopausal, and 18 (31.58%) were < 40 years old. All of the women underwent surgery. A total of 37 women (64.91%) were submitted to complete surgical staging for BOT, and none (0/57) were submitted to pelvic or paraortic lymphadenectomy. Chemotherapy was administered for two patients who recurred. The final histological diagnoses were: serous in 20 (35.09%) cases, mucinous in 26 (45.61%), seromucinous in 10 (17.54%), and endometrioid in 1 (1.75%) case. Intraoperative analyses of frozen sections were obtained in 42 (73.68%) women, of which 28 (66.67%) matched with the final diagnosis. The mean follow-up was of 42.79 months (range: 2.03–104.87 months). Regarding the current status of the women, 45 (78.95%) are alive without disease, 2 (3.51%) are alive with disease, 9 (15.79%) had their last follow-up visit > 1 year before the performance of the present study but are alive, and 1 patient (1.75%) died of another cause.Conclusion Women in the present study were treated according to the current guidelines and only two patients recurred.
Keywords: borderline ovarian tumor (BOT); treatment; fertility sparing surgery; recurrence